Evaluation of a multisectoral intervention to mitigate the risk of severe acute respiratory coronavirus virus 2 (SARS-CoV-2) transmission in long-term care facilities. (5th October 2021) - Vijh, Rohit; Prairie, Jessica; Otterstatter, Michael C.; Hu, Yumian; Hayden, Althea S.; Yau, Brandon; Daly, Patricia; Lysyshyn, Mark; McKee, Geoff; Harding, John; Forsting, Sara; Schwandt, Michael
Abstract: Objective: A Canadian health authority implemented a multisectoral intervention designed to control severe acute respiratory coronavirus virus 2 (SARS-CoV-2) transmission during long-term care facility (LTCF) outbreaks. The primary objective was to evaluate the effectiveness of the intervention 14 days after implementation. Design: Quasi-experimental, segmented regression analysis. Intervention: A series of outbreak measures classified into 4 categories: case and contact management, proactive case detection, rigorous infection control practices and resource prioritization and stewardship. Methods: A mixed-effects segmented Poisson regression model was fitted to the incidence rate of coronavirus disease 2019 (COVID-19), calculated every 2 days, within each facility and case type (staff vs residents). For each facility, the outbreak time period was segmented into an early outbreak period (within 14 days of the intervention) and postintervention period (beyond 14 days following the intervention). Model outputs quantified COVID-19 incidence trend and rate changes between these 2 periods. A secondary model was constructed to identify effect modification by case type. Results: The significant upward trend in COVID-19 incidence rate during the early outbreak period (rate ratio [RR], 1.07; 95% confidence interval [CI], 1.03–1.11; P < .001) reversed during the postintervention period (RR, 0.73; 95% CI, 0.67–0.80; P < .001). The average trend did not differ by case type during the early outbreak period ( P > .05) or the postintervention period ( P > .05). However, staff had a 70% larger decrease in the average rate of COVID-19 during the postintervention period than residents (RR, 0.30; 95% CI, 0.10–0.88; P < .05). Conclusions: Our study provides evidence for the effectiveness of this intervention to reduce the transmission of COVID-19 in LTCFs. This intervention can be adapted and utilized by other jurisdictions to protect the vulnerable individuals in LTCFs.